Experience of Integrated Health Post (Posyandu) Cadres in Addressing Stunting in Toddlers - Maulin Halimatunnisa; D. Mustamu Qamal Pa’ni; Muhamad Rizwan Ayogi; Bq. Fitria Frisma Lita; Iwan Wahyudi; Lalu Hersika Asmawariza (Jurnal Keperawatan Duta Medika, 2026)
Introduction: Stunting is a condition in which children under the age of five experience growth failure due to long-term malnutrition so they are too short for their age. In 2023, the prevalence of stunting in Indonesia will be 21.5%, this condition only decreased by 0.1% from the 2022 data of 21.6%. Optimizing the role of integrated health post cadres is one of the government's efforts to accelerate the reduction in stunting incidence. Objectives:  This study aims to investigate the experiences of integrated health post cadres in addressing stunted children. Methods: This study uses a qualitative phenomenological research design. The research sample was selected using the purposive sampling method, comprising four informants. Data analysis using Colaizzi's (1978) thematic technique analysis. Results:  This research produced four main themes, including cadres as growth and development monitors and the preventive role of toddler nutritional problems, this study produced four main themes including cadres as growth and development monitors and the preventive role of toddler nutritional problems, cadre differentiation perspectives on stunting, high prevalence of stunting, cadres as responsive agents in overcoming stunting.